Synthesis and biological evaluation of novel 1,2,3-triazole hybrids of cabotegravir: identification of potent antitumor activity against lung cancer - Guo, Yajie; Sang, Dan; Guo, Bin; Wang, Dan; Xu, Xinyue; Wang, Huili; Hou, Cuilan; Mao, Longfei; Li, Fang; Li, Sanqiang (Frontiers in Pharmacology, 2023)
In pursuit of discovering novel anticancer agents, we designed and synthesized a series of novel 1,2,3-triazole hybrids based on cabotegravir analogues. These compounds were subjected to initial biological evaluations to assess their anticancer activities against non-small-cell lung cancer (NSCLC). Our findings indicated that some of these compounds exhibited promising antitumor abilities against H460 cells, while demonstrated less efficacy against H1299 cells. Notably, compound 5i emerged as the most potent, displaying an IC 50 value of 6.06 μM. Furthermore, our investigations into cell apoptosis and reactive oxygen species (ROS) production revealed that compound 5i significantly induced apoptosis and triggered ROS generation, ultimately leading to cell death. Additionally, western blot analysis revealed the pronounced elevation of that treatment with compound 5i resulted in a notable increase in LC3 expression in H460 cells and γ-H2AX expression in H1299 cells subsequent to treatment with compound 5i., which may potentially contribute to cell death. These molecular responses potentially contribute to the observed cell death phenomenon. These findings highlight the potential of compound 5i as a promising candidate for further development as an anticancer agent especially lung cancer.